Noise Detection System in The Classroom Using Sound Sensors and NodeMCU ESP6288 - Arif Ainur Rafiq; Sugeng Dwi Riyanto; Hera Susanti (Journal of Electronics Technology Exploration, 2023)
The educational environment is the process of educational activities, so the environment is expected to be comfortable and avoid noise. Noise can be disturbing, such as the ringing of mobile phones or sounds produced by humans. Sound noise in a room can cause loss of concentration, so that indoor activities can be disrupted. Based on these problems, it is necessary to have a tool used to detect the noise level of sound in the classroom. Therefore, a noise detection system in the learning room uses a sound sensor based on NodeMCU ESP8266, which can send email notifications and be monitored through the thinger.io application. The location of this research is in a classroom. This tool consists of hardware (hardware) including NodeMCU ESP8266, PIR Sensor, LCD 16x2 I2C, Sound Sensor, DF Player Mini Mp3, Speaker, and Android application software. The working principle is that if the decibel value exceeds the predetermined value, the room user will hear a warning sound and send an informational text in the form of an email notification. Based on tests on several parameters, testing using the sound of a drilling machine obtained an error value of 8.7%. In music sounds, an error value of 7.7%, and inhuman screaming sounds, an error value of 8.1%. The tool has been successful in the test results and can be implemented in the classroom.